Konsep dan Perlaksanaan Cukai Kharaj Dalam Ekonomi Islam - Daud, Normadiah; Salleh, Siti Fatimah (2010)
Tax is an important element in economics development of a country. For instance, the main tax in the sistem of Islamic economy is the land tax or well-accepted as kharaj. In this writing, the writer tries to highlight the concept, background, islamic law and how kharaj is implemented. Evidently, kharaj gives significant contribution in generating a superb sistem of Islamic economy. Although kharaj in no longer practiced, history has proven its achievement starting from the triumphant era of Sayyidina 'Umar al Khattab and Sayyidina 'Umar Abdul Aziz where these two magnificent Islamic icons were able to eradicate poverty during their administrations. Apparently, this past success should be a valuable guidance to the present Muslim economists in undergoing and overcoming the economics recession.